(untitled) (Revista de História Regional, 2007)
The article is about the strategies of survival and the routine of the prostitutes of Manaus in the Belle Epoque, period of urbanistic and architectural transformation and consolidation of the city in the economy during the rubber boom.The article was drawn with the objetive of showing a dynamic and multiple process, permeated by oppositions, conciliations, permanences and ruptures, drawing profiles of the relationships that involved problems, struggles, experiences, tensions, looking for the multiples senses of the prostitution of the city. The article tries to understand its national, regional, and local importance, therefore asking questions about the hegemonic imaginariy that justified the chauvinism of the Manaus Rubber Boom.